‘E’ of ESG and firm performance: evidence from China - Qian, Binsheng; Poshakwale, Sunil S.; Tan, Yusen (Elsevier, 2024)
Following the ESG rating divergence reported in the previous research studies, we develop a novel firm-level Green Commitment (GC) index by incorporating new dimensions of environmental management and governance. We construct GC scores for all A-share listed companies in China from 2015 to 2021 and analyze whether firms with greater environmental commitment exhibit improvements in their future performance. Our results show that firms with high GC scores achieve higher stock returns without incurring extra risk. Additionally, a strong environmental commitment can enhance operating performance by mitigating financial constraints. The evidence supports the view that environmental investing contributes to the creation of positive shareholder value. Our GC index can be applied more widely to resolve the mixed evidence on the value implications of corporate environmental commitments.
Keywords: 3502 Banking, Finance and Investment; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Finance; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment; 3801 Applied economics; Environmental investing; ESG divergence; Firm performance; Financial constraints; Industry competition; State ownership